Republic of South Sudan : 2022 Article IV Consultation And Second Review Under The Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2022)
South Sudan is a very fragile post-conflict state and one of the most vulnerable countries in the world to climate-driven disasters. The pandemic reversed the economic recovery that followed the 2018 peace agreement. The oil price shock from the pandemic resulted in a massive loss of revenue, causing the government to run up expenditure arrears and resume monetary financing. This led to sharp exchange rate depreciation and runaway inflation. The policies implemented under a Staff Monitored Program (SMP) that was approved in March 2021 and supported by two disbursements under the RCF (in November 2020 and March 2021) have helped restore macroeconomic stability and eliminate a long-standing system of multiple exchange rates. Higher oil prices have dampened the effects of floods on lower oil production and sustained international reserves in the face of a rising import bill. The sharp rise in global food prices risks is exacerbating the dire humanitarian situation in South Sudan, where 70 percent of the population suffers from acute food insecurity, at a time when aid budgets are being cut.